“How and to what extend the premiums of ATE legal expense insurance relate with the value of personal injury cases” - Charalambous, Joanna (2009)
This dissertation investigates the policy of Conditional Fee Arrangements together with After-The-Event insurance and their role for achieving access to justice in the legal compensation system of UK. Despite its recent introduction in the country, arguments and disbeliefs regarding its effectiveness, the level of costs and efficiency for personal injury claims came into sight between the providers of after the event insurance and the liability insurers. The research expands and describes this “cost war” from the first years of introduction until recently and highlights the key differences between the Legal Expense Insurance market of UK and successful countries like Germany. The findings of the paper support the fact that costs tend to influence the levels of ATE premiums in relation to the personal injury claim type as well as that ATE premiums and the Success Fees are the factors that insurance companies and CFA lawyers compensate themselves according to the level of risk that they bear for each personal injury case. Overall on the basis of the evidence, this dissertation argues that factors like disbursement costs, general damages, profit costs; costs that an ATE insurance policy covers, influence ATE premiums and therefore agree to some extend with ATE insurance providers beliefs. What the findings of the paper however caused the author to realize is that perhaps the structure of the UK’s LEI market is not mature enough and may not have the appropriate legislations to function well. Finally the paper concludes with recommendations and suggestions for further work.